(untitled) - Kamarul Md Shah, Jaharudin Padli, Jasmi Abu Talib, Farah Mukhtar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Well-being is an important aspect of the life of every human being. This study emphasized the aspects of well-being, especially psychological well-being among students at one of the higher learning institutes in Malaysia. This study also attempted to provide a definition of well-being and dimensions or construct of well-being in the perspective of the students at the higher learning institute. This is a qualitative design which the case study was conducted using structured interviews. The sample of this study consisted of group of student leaders, group of excellent students in academic (based on CGPA), and group of excellent students in co-curriculum. The study data were analyzed using NVivo10 software. The findings show that there are three main themes encompassing six dimensions that are environmental control, personal growth, purpose of life, self-acceptance, autonomy, and positive relationships with others. These themes were supported by the subjectivity of the research subjects according to their respective perspectives. The results of this study are important for the higher learning institution and the Malaysia Ministry of Education (MOE) to find the most appropriate and effective method of student psychological well-being in building a generation that is capable of achieving strong self-development and ready for future challenges.